Temporal Features of Psychological and Physical Self-Representation: An ERP Study - Liu, Lei; Li, Wenjie; Li, Jin; Lou, Lingna; Chen, Jie (Frontiers in Psychology, 2019)
Psychological and physical self are two important aspects of self-concept. Although a growing number of behavioral and neuroimaging studies have investigated the cognitive mechanism and neural substrate underlying psychological and physical self representation, most of the existing research on psychological and physical self representation had been done in isolation. The present study aims to examine the electrophysiological responses to both psychological (one`s own name) and physical (one`s own voice) self-related stimuli in a uniform paradigm. Event-related potentials (ERPs) were recorded for subjects` own and others` names uttered by subjects` own or others` voice (own voice-own name, own voice-other`s name, other`s voice-own name, other`s voice-other`s name) while subjects performed an auditory passive oddball task. The results showed that one`s own name elicited smaller P2 and larger P3 amplitudes than those of other`s names, irrespective of the voice identity. However, no differences were observed between self and other`s voice during the P2 and P3 stages. Moreover, an obvious interaction effect was observed between voice content and voice identity at the N400 stage that the subject`s own voice elicited a larger parietal N400 amplitude than other`s voice in other name condition but not in own-name condition. Taken together, these findings suggested that psychological (one`s own name) and physical (one`s own voice) self-representation induced distinct electrophysiological response patterns in auditory-cognitive processing.